Pengaruh Penggunaan Game Edukasi Berbasis Digital Terhadap Pemahaman Konsep Sains - Mukminah; Yolanda Aprilianti; Herjan Haryadi (STAI AL-AMIN, 2025)
This study aims to determine the effect of using digital educational games on the understanding of science concepts among fifth-grade students at SDN 3 Gunungsari. This research uses a quantitative approach with a quasi-experimental design (nonequivalent control group design). The sample consists of two classes: the experimental class used the educational game